Stability Evaluation of Rabigh Concrete Gravity Dam - Alzahrani, Abdullah; Bahabri, Abdulelah; Almuntshry, Nawaf; Abulqadim, Tuhami; Sabtan, Abdulah (Journal of King Abdulaziz University-Meteorology Environment and Arid Land Agriculture Sciences, 2024)
Concrete dams are constructed for holding big volume of water for various uses. In terms of economic and social development, they viewed it as a critical component of the country’s infrastructure for flood control, hydropower generation and water transportation, irrigation, and water delivery. Stability is usually a major issue in the dam of gravity dams, and if there are any weak structural planes in the dam that might cause failure (Ghanizadeh and Ghanizadeh, 2017). Rabigh dam (RD) is the third important dam in Saudi Arabi, located in the eastern side of the Red Sea. It was built in 1987 and intended to protect Rabigh industrial city and recharging the groundwater. RD is a concrete gravity type, 81 m high with a huge reservoir of 229 million m3. The reservoir has a permanent dead water load at a level of 63 m (minimum water level), and discharges flood water through a sufficient spillway at an elevation of 71 m (maximum water level). The main objective of this study is to reevaluate the dam stability. Gravity dams, in general, are subjected to two hydraulic forces (the lateral water force, Fw and the uplift, U) in addition to sedimentation (Sd) and their stability relies on its self-weight (Wt.). Several recent research warned of an expected increase of rainwater and flood frequency due to global warming, which will raise the destabilizing forces while the dam weight (Wt.) is constant. RD possible movement during its normal operation was checked in two conditions: dam overturning and sliding. The possibility of dam overturning was tested at two water levels behind the dam; at 63 (the dead load level) and 71.5 m (the spillway level), the resulting factor of safety (Fs) are 1.85 and 1.50 respectively. The stability against dam sliding was evaluated at the same water levels giving a save Fs-value of 1.51 at the lower level and 1.23 at the higher one. On the other hand, the acting forces introduce compressive and tensile stresses on dam body of 188.9 t/m2 and 12 t/m2, respectively. The internal stresses which may develop in the dam body is much less than the allowable limits.